Step-by-step explanation:
![1.\sum_{i=1}^{5}3i](https://tex.z-dn.net/?f=1.%5Csum_%7Bi%3D1%7D%5E%7B5%7D3i)
The simplest method is "brute force". Calculate each term and add them up.
∑ = 3(1) + 3(2) + 3(3) + 3(4) + 3(5)
∑ = 3 + 6 + 9 + 12 + 15
∑ = 45
![2.\sum_{k=1}^{4}(2k)^{2}](https://tex.z-dn.net/?f=2.%5Csum_%7Bk%3D1%7D%5E%7B4%7D%282k%29%5E%7B2%7D)
∑ = (2×1)² + (2×2)² + (2×3)² + (2×4)²
∑ = 4 + 16 + 36 + 64
∑ = 120
![3.\sum_{k=3}^{6}(2k-10)](https://tex.z-dn.net/?f=3.%5Csum_%7Bk%3D3%7D%5E%7B6%7D%282k-10%29)
∑ = (2×3−10) + (2×4−10) + (2×5−10) + (2×6−10)
∑ = -4 + -2 + 0 + 2
∑ = -4
4. 1 + 1/4 + 1/16 + 1/64 + 1/256
This is a geometric sequence where the first term is 1 and the common ratio is 1/4. The nth term is:
a = 1 (1/4)ⁿ⁻¹
So the series is:
![\sum_{j=1}^{7}(\frac{1}{4})^{j-1}](https://tex.z-dn.net/?f=%5Csum_%7Bj%3D1%7D%5E%7B7%7D%28%5Cfrac%7B1%7D%7B4%7D%29%5E%7Bj-1%7D)
5. -5 + -1 + 3 + 7 + 11
This is an arithmetic sequence where the first term is -5 and the common difference is 4. The nth term is:
a = -5 + 4(n−1)
a = -5 + 4n − 4
a = 4n − 9
So the series is:
![\sum_{j=1}^{5}(4j-9)](https://tex.z-dn.net/?f=%5Csum_%7Bj%3D1%7D%5E%7B5%7D%284j-9%29)
Answer:
Step-by-step explanation:
y = ax² + bx + c
~~~~~~~
(4, - 2), (8, 6), (2, 0)
a(4²) + b(4) + c = - 2
a(8²) + b(8) + c = 6
a(2²) + b(2) + c = 0
16a + 4b + c = - 2 .............. <em>(1)</em>
64a + 8b + c = 6 ............... <em>(2)</em>
4a + 2b + c = 0 ................. <em>(3)</em>
a = 0.5 ; b = - 4 ; c = 6
<em>y = 0.5x² - 4x + 6</em>
Part A: (0, 6), (6, 0)
Part B: (0,6)
Part C: (6, 0)
Part D: [ 4, ∞ )
The factors of 21 are 1, 3, 7, and 21
Answer:
the answer for this question is non-linear
Step-by-step explanation:
linear means in a <u><em>straight</em></u> line. the question you wrote is <u>NOT</u> in a strait line.
hoped the answer helped